Re-evaluation and typification of Foeniculum piperitum (Apiaceae), an underknown medicinal plant and crop wild relative - Ilardi, Vincenzo; Troia, Angelo (Phytotaxa, 2021)
Foeniculum piperitum was described as Anethum piperitum based on plants collected in Sicily, Italy. Currently it is treated either as a synonym of Foeniculum vulgare, or as one of two subspecies within that taxon. Here we show that F. vulgare and F. piperitum are two different, sometimes co-occurring, taxa and that given clear morphological and ecological separation, they should be treated as distinct species. Anethum piperitum is typified. Owing to misapplication of names and wrong synonymizations, the ecology and chorology of F. vulgare and F. piperitum have to be better defined.